2020
DOI: 10.3390/su12020514
|View full text |Cite
|
Sign up to set email alerts
|

Young People Collecting Natural Souvenirs: A Perspective of Sustainability and Marketing

Abstract: Collecting of natural souvenirs causes destruction of the natural environment as well as social and economic problems. The article shows that the next generation will have a tendency to aggravate such problems by collecting natural souvenirs. To discover the preferences of young people related to collecting natural souvenirs, the authors performed a survey in Poland on a sample of 426 persons aged 21–30. The survey has shown that 80.7% of young people participating in tourist trips bring souvenirs to their pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Even if over‐collection and trade of marine curio has been identified as a driving force in biodiversity and habitat degradation with consequent loss of related ecosystem services (Gössling et al, 2004; Kowalewski et al, 2014), there is little scientific data on this phenomenon especially for the Mediterranean Sea. More specifically, there are no studies focusing on natural mementos, that is, souvenirs not purchased as manufacture of crafts or as marine curiosities, but directly collected by tourists in the wild (Dias et al, 2011; Pabian et al, 2020). This activity seems to be widespread and with high environmental and socio‐economic impacts (Kowalewski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even if over‐collection and trade of marine curio has been identified as a driving force in biodiversity and habitat degradation with consequent loss of related ecosystem services (Gössling et al, 2004; Kowalewski et al, 2014), there is little scientific data on this phenomenon especially for the Mediterranean Sea. More specifically, there are no studies focusing on natural mementos, that is, souvenirs not purchased as manufacture of crafts or as marine curiosities, but directly collected by tourists in the wild (Dias et al, 2011; Pabian et al, 2020). This activity seems to be widespread and with high environmental and socio‐economic impacts (Kowalewski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Wildlife governance as well as regulation and its enforcement vary across countries, regions and communities, as do tourists compliance on the base of their origin and related cultural, social, and economic conditioning. A study performed in Poland showed that female tourists are more engaged than male tourists in seashell collection and that 100 g corresponds to the average personal quota (Pabian et al, 2020). Another survey in Tanzania by Gössling et al (2004) quantified that 39% of tourists collected shells in Zanzibar and only 7% had bought them (2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations